Genetic diversity of the Algerian peanut population analyzed using morphological markers and seed storage proteins - H. Djeghim; I. Bellil; D. Khelifi (Труды по прикладной ботанике, генетике и селекции)
Background. The peanut is one of the most important oil crops suitable for cultivation in the tropical areas of the world. Despite its agronomic importance, few studies have been carried out to assess the morphogenetic diversity of Arachis hypogaea L., especially in East African countries. The major interest of this morphologic study lies in the potential of this species to provide useful genes for the improvement of cultivated peanuts. To date, no study has been performed in Algeria to characterize local peanut varieties.Materials and methods. Thirty peanut accessions were collected from four principal areas of peanut production in Algeria. Genetic characterization using 15 agronomic characters and 25 morphological descriptors showed a high level of diversity among accessions. Principal Component Analysis and the Hierarchical Ascendant Classification were made to clarify the genetic relationship between peanut accessions.Results and discussion. Results showed that leaflet size (length and width), seed shape and size, oil content, and branching pattern were the principal characters to discriminate the screened A. hypogaea accessions. In addition to that, the weights of 10 pods and 100 seeds were the most variable traits and presented a CV of 42.53% and 40.12%, respectively. On the other hand, total storage proteins extracted were separated using SDS-PAGE and revealed thirty bands that were used to generate a matrix and make a cluster analysis using the UPGMA method, exhibiting different storage proteins compositions. Moreover , the phenotypic diversity observed agrees with the storage protein profile diversity, while the accessions grouped in similar clusters belong to the two subspecies of A. hypogaea. The results of the current study show that morphological traits and seed storage proteins can be useful for exploring the diversity among A. hypogaea accessions.